Tinjauan dan Pendampingan Strategi Display Produk Pada Alfamart - Mawardi, Mawardi; Yusdira, Ade; Mashadi, Mashadi (Jurnal Abdimas Dedikasi Kesatuan, 2025)
Product display is a way of structuring products, especially target products that are applied by certain companies to attract consumer interest. Product display has an important role for a company, especially companies engaged in retail. Arranging products using good techniques and concepts, of course, will produce an attractive appearance and be able to become a magnet for consumers and buy the displayed products. With this product display, it will certainly have a positive impact on the company, especially in increasing sales and sales. The objectives are to find out: 1) how to implement product display at Alfamart; 2) what are the obstacles in the view; 3) how to overcome obstacles in implementing product displays at Alfamart. The results are: 1) displays used by Alfamart: floor displays, vertical displays, wall displays, impulse buying displays, mixed merchandise displays, cut box displays, mixed displays, edge displays, special displays, island displays, and various product displays. ; 2) obstacles, namely the lack of human resources and an irregular task schedule; 3) in overcoming display barriers, namely by adding employees in the sales clerk and making a display task schedule, so that the display can run smoothly and in accordance with company expectations.   Keywords: display product, Alfamart